Toward absolute viability measurements for bacteria. Issue 12 (27th September 2021) - Dunkers, Joy P.; Iyer, Hariharan; Jones, Brynna; Camp, Charles H.; Stranick, Stephan J.; Lin, Nancy J.
Abstract: We aim to develop a quantitative viability method that distinguishes individual quiescent from dead cells and is measured in time (ns) as a referenceable, comparable quantity. We demonstrate that fluorescence lifetime imaging of an anionic, fluorescent membrane voltage probe fulfills these requirements for Streptococcus mutans . A random forest machine‐learning model assesses whether individual S. mutans can be correctly classified into their original populations: stationary phase (quiescent), heat killed and inactivated via chemical fixation. We compare the results to intensity using three models: lifetime variables (τ1, τ2 and p1 ), phasor variables ( G, S ) or all five variables, with the five variable models having the most accurate classification. This initial work affirms the potential for using fluorescence lifetime of a membrane voltage probe as a viability marker for quiescent bacteria, and future efforts on other bacterial species and fluorophores will help refine this approach. Abstract : Viability of quiescent microbes is an important but elusive property to measure, and even more difficult to quantify using referenceable units for comparability. Here, we present a study using fluorescence lifetime imaging microscopy of a membrane‐voltage fluorophore incubated with an oral microbe, Streptococcus mutans, and demonstrated differences in lifetime response of individual microbes in a quiescent state (SP) compared to those killed using heat (HK) or chemical fixation (FP).